The life of Jews in Poland before the Holocaust : a memoir - Gold, Ben-Zion (University of Nebraska Press, 2007)
Ben-Zion Golds memoir brings to life the world of a million Jews in pre-World War II Poland who were later destroyed by the Nazis. Warmly recalling the relationships, rituals, observances, and celebrations, Gold evokes the sense of family and faith that helped him through the catastrophe that followed.